Weakly Nearly Quasi Prime Submodules - Hero Jumaa Hassan; Haibat K. Mohammad Ali (Tikrit Journal of Pure Science, 2022)
In this paper, all rings are commutative with identity, and all R-modules are unitary Left R-modules. We introduce the concept WNQP submodule as new generalizations of weakly quasi prime submodule and give basic properties, examples and  characterizations of this concept.